The Italian Experience with Halal Certification: the Case of Halal Italia (Stato, Chiese e pluralismo confessionale, 2020)
SUMMARY: 1. Introduction - 2. Brief Remarks on the Notion of Halal - 3. The Interests at Stake in Halal Certification - 4. Actors and Instruments Involved in Halal Certification - 5. The Constitutional Regulation of the Religious Factor and Its Impact on Halal Certification - 6. Halal Italia and the 2010 Inter-Ministerial Convention - 7. Conclusion.ABSTRACT: The purpose of this paper is to examine the Italian experience with halal certification and, in particular, the case of Halal Italia. After some brief preliminary remarks on the notion of halal, I will examine the general context of halal certification, by focusing on the interests at stake and on the actors and instruments involved. Next, I will take into account the impact of the constitutional regulation of the religious factor on halal certification. Finally, my analysis will turn to the trademark Halal Italia and the 2010 Inter-Ministerial Convention.